2017
DOI: 10.1128/aac.01106-17
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ceftriaxone, Cefepime, Doxycycline, Ciprofloxacin, and Combination Therapy for Vibrio vulnificus Foodborne Septicemia

Abstract: Foodborne infections are associated with higher rates of sepsis and mortality than wound infections; however, antibiotic efficacy studies have not been performed in foodborne infection models. The efficacies of ceftriaxone, cefepime, doxycycline, ciprofloxacin, and combination therapy were assessed in intestinal infection in mice in order to model foodborne infections. In accordance with prior studies of cefotaxime, cefepime was synergistic with doxycycline and ciprofloxacin ; combination therapy significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Prompt treatment with appropriate antimicrobial is essential for the best prognosis. It has already been demonstrated that the use of quinolone alone or the combination of tetracycline and third generation cephalosporin had the lowest mortality and should be the priority selection for V. vulnificus infection [11,12]. However, V. vulnificus infection may be increasingly difficult to treat as the inappropriate use of antimicrobials has increased resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Prompt treatment with appropriate antimicrobial is essential for the best prognosis. It has already been demonstrated that the use of quinolone alone or the combination of tetracycline and third generation cephalosporin had the lowest mortality and should be the priority selection for V. vulnificus infection [11,12]. However, V. vulnificus infection may be increasingly difficult to treat as the inappropriate use of antimicrobials has increased resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Although Vibrio vulnificus isolates were recorded susceptible to ampicillin, amikacin, ceftazidime, ceftriaxone, cefuroxime, ciprofloxacin, gentamicin, imipenem, piperacillin, and sufamethoxazoletrimethoprim by clinical microbiology laboratory, many countries demonstrated a small porportion of clinical isolates resistance to penicillin, ampicillin, amoxicillin, streptomycin, cephalexin and erythromycin (29,30). In a study by Trinh et al, the survival rate was significantly higher with ceftriaxone-doxycycline (91%), ceftriaxone-ciprofloxacin (100%), cefepime-doxycycline (96%), and cefepime-ciprofloxacin (90%) combination therapy for Vibrio vulnificus septicemia (31). But otherwise recent literatures indicated that Aeromonas spp.…”
Section: Monomicrobial Necrotizing Fasciitis and Bacteremia Caused Bymentioning
confidence: 99%
“…An animal experiment suggested that the combination of ciprofloxacin and cefotaxime is an effective treatment option for V. vulnificus -infected people [ 39 ]. A recent study suggested that cefepime combined with doxycycline or ciprofloxacin should be initiated to cover gram-negative-resistant organisms and V. vulnificus while awaiting a microbiological diagnosis; once a diagnosis of V. vulnificus septicemia is confirmed, treatment can be safely changed to ceftriaxone combined with doxycycline or ciprofloxacin [ 42 ]. Another recent study suggested that tigecycline alone might be a better therapeutic option than a traditional combination regimen of ceftazidime plus doxycycline in patients with V. vulnificus infection [ 43 , 44 ].…”
Section: Treatmentmentioning
confidence: 99%